ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN PERTAMBANGAN BATUBARA - SAFITRI NURHIDAYATI (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2020)
ABSTRACT (Times New Roman 12 Point) The purpose of this thesis is to find out which coal mining companies listed on the Indonesia Stock Exchange that are predicted not to go bankrupt, are predicted to be in a gray area and are predicted to go bankrupt in the 2015-2017 period based on analysis using the Altman Z-Score method. The object of research is twenty-two coal mining companies. The data used in this study is a summary of the company's annual financial statements that are listed on the Indonesia Stock Exchange. The analysis technique used is the Altman Z-Score bankruptcy prediction model using the formula Z